Protein Programmed Death-Ligand 1 Expression in Non-Small Cell Lung Cancer (NSCLC) and Its Correlation to Smoking Status in North Sumatera Population - Noni Novisari Soeroso; Setia Putra Tarigan; Rahmat Hidayat; Elisna Syahruddin; Evlin Suzanna; Dian Chayadi (Talenta Publisher, 2024)
Background: Tobacco smoking is associated to the increase risk of lung cancer, and smoking could also trigger the tumour proportion score from programmed death ligand (PD-L1). Objective: This study aims to identify the correlation of non-small cell lung cancer (NSCLC) with the PD-L1 expression and smoking profile on the North Sumatra Population. Methods: This research implemented a descriptive study with cross-sectional design. Results: This study was carried out from August 2019 to September 2020. Results: Characteristics of patients with NSCLC to the PD-L1 expression were found more in male patients with percentage of 88.6%, whereas the most common type of cancer is adenocarcinoma, accounting for 97.14% of cases with mild degree smoking index for 45.7% (Brinkman index) and IV-stage of clinical status for 68.6%. The tumour proportion score with 1-49% was 51.4% with high expression of PD-L1 (positive) for 74.28%, while lower expression of PD-L1 accounted for 45%. Conclusion: There is a correlation between PD-L1 expression and smoking status in NSCLC patients, with p-value of 0.037 (<0.05).